Green Pressure, Lean Measures: Unveiling Corporate Downsizing Within the European Union Emissions Trading System - Boeckx, Jana; Struyfs, Kristof; Torsin, Wouter (Journal of Financial and Quantitative Analysis, 2025)
In 2017, the European Union Emissions Trading System underwent a policy intervention that resulted in a surge in carbon prices. Using this setting as a quasi-natural experiment, we focus on employment, productivity, and emission outcomes among covered enterprises. Results show that emission-intensive private firms, particularly those with financial constraints, are more likely to downsize by divesting production assets, reducing both workforce and emissions. Smaller, cash-strapped listed firms are also prone to downsize by decreasing their operating leverage while maintaining emission output and asset levels. Positive productivity outcomes indicate that both private and listed firms become leaner postintervention.